State Hospital - Kienholz, Edward
A room in which mentally ill patients are strapped to a bed. Cast plaster and fiberglass figures, hospital beds, bedpan, hospital table, goldfish bowls, live goldfish, lighted neon tubing, steel hardware, wood, paint.